Binge drinking differentially affects cortical and subcortical microstructure. (20th January 2017) - Morris, Laurel S.; Dowell, Nicholas G.; Cercignani, Mara; Harrison, Neil A.; Voon, Valerie
Abstract: Young adult binge drinkers represent a model for endophenotypic risk factors for alcohol misuse and early exposure to repeated binge cycles. Chronic or harmful alcohol use leads to neurochemical, structural and morphological neuroplastic changes, particularly in regions associated with reward processing and motivation. We investigated neural microstructure in 28 binge drinkers compared with 38 matched healthy controls. We used a recently developed diffusion magnetic resonance imaging acquisition and analysis, which uses three‐compartment modelling (of intracellular, extracellular and cerebrospinal fluid) to determine brain tissue microstructure features including neurite density and orientation dispersion index (ODI). Binge drinkers had reduced ODI, a proxy of neurite complexity, in frontal cortical grey matter and increased ODI in parietal grey matter. Neurite density was higher in cortical white matter in adjacent regions of lower ODI in binge drinkers. Furthermore, binge drinkers had higher ventral striatal grey matter ODI that was positively correlated with binge score. Healthy volunteers showed no such relationships. We demonstrate disturbed dendritic complexity of higher‐order prefrontal and parietal regions, along with higher dendritic complexity of a subcortical region known to mediate reward‐related motivation. The findings illustrate novel microstructural abnormalities that may reflect an infnce of alcohol bingeing on critical neurodevelopmental processes in an at‐risk young adult group. Abstract : Chronic or harmful alcohol use is associated with neuroplastic changes, particularly in regions associated with reward processing and motivation. Binge drinkers demonstrated disturbed neurite complexity in the dorsolateral prefrontal cortex and parietal regions, as measured by Neurite Orientation Dispersion and Density Imaging. Heightened neurite complexity in the ventral striatum of binge drinkers was associated with a more severe binge‐like pattern of alcohol consumption. Disturbed microstructure in cortical and subcortical regions may reflect a disruption in higher‐order prefrontal control systems and enhanced involvement of reward‐related motivational systems.